A coach development program: A guided online reflective practice intervention study - Da Silva, E. J.; Mallett, C. J.; Sánchez-Oliva, D.; Dias, A.; Palmeira, A. (Journal of Sports Sciences, 2022)
Coaches can influence athlete outcomes, such as performance and personal development; yet, coaches themselves are learners in their own right, who seek to develop their coaching craft. Reflective practice is essential for coaches` development; however, coaches might engage and benefit from reflective practice in myriad ways. This study aimed to evaluate if online reflective journaling (ORJ) enhances the depth of reflection of sports coaches in a 4-week coach development programme (CDP). Participants were a convenience sample of 83 sports coaches from several sports, divided into an intervention group (N = 42) and a control group (N = 41). Data collection used a mixed-methods approach, examining a CDP focused on the coaches` reflective practice. The results revealed that reflection was the only dependent variable that showed significant differences over time. Participation in ORJ showed positive effects on reflection in both groups; however, only the experimental group was statistically significant. For this sample, ORJ was found to help enhance coaches` reflection towards critical reflection. All texts included in pre-, post-, and follow-up tests were coded for trustworthiness purposes. This finding supports the potential of ORJ in nurturing reflective practice, which is considered a core competency in becoming a successful sports coach.